Research on Cross-Platform Motion Control System Based on gSOAP - Tang, Hao; Wu, Zhezhou; Xu, Bo; Bhatti, Uzair Aslam; Yu, Mingtian; Lu, Yong (2024 7th International Conference on Pattern Recognition and Artificial Intelligence (PRAI), 2024)
Traditional industrial motion control systems usually use local PCs to connect with the controller through cables. For the shortcomings of this kind of control system, such as strong platform dependence and restricted control territory, a generalized motion control system that can be cross-platform and more flexible in application is proposed. Firstly, the WebService service of controller API is generated by gSOAP tool and deployed on Linux system containing real-time preemption patch PREEMPT_RT, and the communication between non-real-time and real-time processes of API instruction call is completed by naming FIFO, and the functions of control instruction parsing, motion control interpolation and axis output control are completed. Finally, experiments show that the motion control system based on gSOAP can realize reliable cross-platform and cross-region control connection, and the human-computer interaction interface can be quickly customized at any time according to the demand without being limited to any device. The new motion control system operates in a more flexible and efficient way, and can better meet the development needs of personalized, intelligent and flexible production.